2017
DOI: 10.1080/17483107.2016.1278473
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity movement reliability and validity of the Kinect version 2

Abstract: Simple transformations of Kinect data could bring magnitudes in line with those of the VMC, allowing the Kinects to be used in a clinical setting. Implications for Rehabilitation The clinical implications of the investigation support the notion that the Kinects could be used in the clinical setting if an understanding of their limitations exists. Using the Kinects to make assessments with a given data collection session is acceptable. Using the Kinects to make comparisons across different days such as before o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…In the study of Reither et al [113] upper extremity movements, mainly of the shoulder joint were measured using the skeleton streams of both versions of the Kinect and compared to a Video Motion Capture (VMC) system. The data was filtered with a fourth order Butterworth filter at 6 Hz.…”
Section: Discussion: Accuracy and Precisionmentioning
confidence: 99%
“…In the study of Reither et al [113] upper extremity movements, mainly of the shoulder joint were measured using the skeleton streams of both versions of the Kinect and compared to a Video Motion Capture (VMC) system. The data was filtered with a fourth order Butterworth filter at 6 Hz.…”
Section: Discussion: Accuracy and Precisionmentioning
confidence: 99%
“…Wang et al, [ 12 ] recruited 10 participants to evaluate Kinect v1 and Kinect v2 for pose tracking accuracy. Reither et al [ 15 ], measured the accuracy of Kinect for ROM measurement using 1 participant in two sessions with four repetitions. Regarding the number of samples per exercise, a static exercise is recommended to be held for 10 to 30 seconds [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They compared the position of hands and feet obtained from motion capture and Kinect, and found errors in the range of 5–7 cm. Reither et al [ 15 ], compared the reliability and validity of Kinect v1 and Kinect v2 based on a Video Motion Capture (VMC) system for upper extremity movements. They showed that ROM magnitudes for both Kinects were different from the VMC, but, the patterns of motion were correlated for both devices.…”
Section: Introductionmentioning
confidence: 99%
“…The Microsoft Kinect (Microsoft Corp., Redmond, WA, USA) is a low-cost, off-the-shelf motion sensor originally designed for video games that can be adapted for quantitative assessment of UE clinical movements [ 9 , 10 , 11 , 12 ]. The measurement abilities of the first-generation Kinect (K1) have been established for UE movements, spatiotemporal gait variables, standing balance, postural control, and even static foot posture [ 9 , 10 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abilities of the second-generation Kinect (K2) are not as robustly established, but have been investigated for some UE, gait, and postural movements [ 11 , 16 , 17 ]. A recent study within our laboratory found both sensors to be valid relative to the gold standard of a VMC system when measuring reaching (forward and side) and angular shoulder movements (frontal, transverse, sagittal) [ 12 ]. Both sensors have also been frequently used within our laboratory for virtual reality (VR)-based motor rehabilitation aimed at improving UE motor abilities of persons with various impairments [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%